Sustainability and well-being indicators - Eric Neumayer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper provides a review and critical discussion of indicators, which attempt to combine the measurement of sustainability with that of well-being. It starts with some commonly agreed definitions of sustainability, showing how most well-being indicators tell us little if anything at all about this issue. Sustainability is most commonly defined in economics as non-declining utility or well-being over time. Yet, due to its future orientation, most indicators of sustainability such as Genuine Savings (GS) have merely focused on the capacity to provide utility in the future, but have not included the measurement of current well-being. Indicators of well-being such as the Human Development Index (HDI), on the other hand, have typically failed to account for sustainability in their measurement of current well-being. The paper then critically reviews the Index of Sustainable Economic Welfare (ISEW) and the Genuine Progress Indicator (GPI), which are the most prominent examples of an indicator, which attempts to fully integrate the measurement of welfare with that of sustainability into one single indicator. Such an integration, whilst seemingly attractive, is rendered difficult by the fact that what contributes to current well-being need not contribute at all or in the same way to sustainability and vice versa. We also review various proposals of extending a welfare indicator, namely the HDI, with sustainability considerations without full integration of both concepts. All of these proposals suffer from a range of fundamental conceptual problems. As one possible alternative, we propose a combination of the HDI and GS, which holds great promise for an assessment of wellbeing and its sustainability, particularly in developing countries. – environment ; sustainable ; measurement
Keywords: I32; Q51; Q56; 330; Nachhaltige Entwicklung; Entwicklungsindikator